If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 = 116 Reorder the terms: -1 + 9x = 116 Solving -1 + 9x = 116 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9x = 116 + 1 Combine like terms: -1 + 1 = 0 0 + 9x = 116 + 1 9x = 116 + 1 Combine like terms: 116 + 1 = 117 9x = 117 Divide each side by '9'. x = 13 Simplifying x = 13
| 9x-57.6=x | | -14x+3(2x-5)=-19-7x | | 4x-20=6x-40 | | 0.3x+0.5=-1.3 | | 3(n-5)=.4-.2(n-7) | | 2y+4=2x | | -12x^2-144x-216=0 | | 32-7x=14+11x | | 44+3x=(X+20) | | 78=5y | | 6x-7=3x+4 | | 6(x-6.5)=9.6 | | 0.2x=0.3 | | 19-4(x+4)=11(x+2)-1 | | 2+(-5)(h+3)=-28 | | -4y+4x=12 | | -3d=13 | | 2+(-5)(h+3)=28 | | y=10000+1x | | 4z-5z+6= | | 9(8x-9)=-351 | | -3y+2y+5=12 | | -4+3c+6=2c+2+c | | 2(x-5)+7=6x-4(1+x) | | 8(c-2)+4=3+c-15 | | 4x+6.46=2x+10 | | x^2-30x-63=0 | | 0.2x+0.1=0.12-0.06 | | 2x-17=14x+1 | | 10x-7=3x+8 | | 6x-(2x+8)=3x+(x+6) | | y=0-5x |